2019
DOI: 10.1136/ijgc-2018-000029
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes of endometrial cancer patients with paraaortic lymph node metastasis: a multi-institutional analysis

Abstract: ObjectiveTo analyze the prognostic factors and treatment outcomes in endometrial cancer patients with paraaortic lymph node metastasis.MethodsData from four centers were collected retrospectively for 92 patients with endometrial cancer treated with combined radiotherapy and chemotherapy or adjuvant radiotherapy alone postoperatively, delivered by either the sandwich or sequential method. Prognostic factors affecting overall survival and progression-free survival were analyzed.ResultsThe 5-year overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…As the lymphatic spread may course from the upper paracervical pathway to the common iliac lymph nodes and then posteriorly to the para-aortic lymph nodes, and as the incidence of para-aortic lymph node metastasis is small,24 stage IIIC1 and stage IIIC2 patients are often treated similarly and outcomes are often analyzed altogether. However, recent studies suggest that prognosis among stage III patients differ; the 5-year overall and progression-free survival rates in stage IIIC2 patients were 35% and 33%, which were significantly lower than those in stage IIIC1 patients 25. In our retrospective study setting, where most of the patients received both SLN biopsy and validation lymphadenectomy, the prevalence of stage III disease was 12.1% and that of stage IIIC2 subset was 5.0%, which were comparable to the previously reported rates 26.…”
Section: Discussionmentioning
confidence: 88%
“…As the lymphatic spread may course from the upper paracervical pathway to the common iliac lymph nodes and then posteriorly to the para-aortic lymph nodes, and as the incidence of para-aortic lymph node metastasis is small,24 stage IIIC1 and stage IIIC2 patients are often treated similarly and outcomes are often analyzed altogether. However, recent studies suggest that prognosis among stage III patients differ; the 5-year overall and progression-free survival rates in stage IIIC2 patients were 35% and 33%, which were significantly lower than those in stage IIIC1 patients 25. In our retrospective study setting, where most of the patients received both SLN biopsy and validation lymphadenectomy, the prevalence of stage III disease was 12.1% and that of stage IIIC2 subset was 5.0%, which were comparable to the previously reported rates 26.…”
Section: Discussionmentioning
confidence: 88%
“…To our knowledge, there was no article mentioned about the comparison between sandwich and concurrent CRTs. Similarly, Onal et al reported a superiority of sandwich CRT in PFS and OS, compared with sequential CRT or radiotherapy only [ 8 , 9 ]. The underlying mechanism explaining the finding about the superiority of sandwich CRT is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…319 Multiple retrospective studies indicated a survival benefit in patients with advanced stage endometrial carcinoma treated with post-operative combined treatment including radiotherapy and chemotherapy, delivered by either the sandwich or sequential method, compared with radiotherapy alone or chemotherapy alone. [326][327][328][329][330][331][332][333][334][335][336][337][338][339][340][341][342][343][344] The benefit of added chemotherapy is unclear for patients with stage I-II clear cell carcinomas. These have often been included with serous as 'non-endometrioid carcinomas'.…”
Section: High Riskmentioning
confidence: 99%